2021
DOI: 10.1177/09726527211045759
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Banking Industry Stability: How Do BRICS and G7 Compare?

Abstract: This study examines banking industry stability in BRICS and G7 from the period 2005 to 2014. The results show that stability level in a prior period affects stability in the subsequent period. Also, the study reveals that competition improves stability, which validates the competition-stability proposition. Economic growth enhances stability in BRICS but not in G7. Inefficiency weakens stability in BRICS; however, its impact in G7 is insignificant. Profitability, capitalization, and inflation enhance stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Borri and di Giorgio (2021) uncovered that during the COVID-19 pandemic, sovereign default risks greatly influenced the contribution of banks to systemic risk. Similarly, Oredegbe's (2022) research on the stability of the banking industry in BRICS and G7 countries revealed a correlation between past and future stability, lending support to the competition-stability hypothesis. This study also noted varying influences of economic growth, inefficiency, and financial factors between BRICS and G7 countries.…”
Section: Banking Market During Crisismentioning
confidence: 71%
“…Borri and di Giorgio (2021) uncovered that during the COVID-19 pandemic, sovereign default risks greatly influenced the contribution of banks to systemic risk. Similarly, Oredegbe's (2022) research on the stability of the banking industry in BRICS and G7 countries revealed a correlation between past and future stability, lending support to the competition-stability hypothesis. This study also noted varying influences of economic growth, inefficiency, and financial factors between BRICS and G7 countries.…”
Section: Banking Market During Crisismentioning
confidence: 71%
“…From the above models, the dependent variable is market power, which is measured by the Lerner Index. Oredegbe (2021) used the inverse of the Lerner index to measure competition. In this study, we apply the economic procedure of Delis (2012) and Brissimis and Delis (2014), we do not include here all the technical details for the estimation process, but we provide a brief definition of the Lerner Index.…”
Section: Methodology and Datamentioning
confidence: 99%